PREDIKSI KASUS COVID-19 DI INDONESIA MENGGUNAKAN METODE BACKPROPAGATION DAN REGRESI LINEAR - Wahyudin Wahyudin; Heri Purwanto (Journal of Information System, Applied, Management, Accounting and Research, 2021)
The emergence of COVID-19 first attacked humans in Wuhan, China, while in Indonesia itself, it began to attack on March 2, 2020 when two people were confirmed positive. From these cases every day has a relatively significant increase. The corona virus is spreading very quickly, therefore the WHO or the World Health Organization decided that the COVID-19s will become a pandemic off March 11, 2020. The corona virus is rising very fast, so immediate response is needed. The corona virus can easily spread and can attack humans regardless of age. Seeing the rapid spread of the virus, finally the governments of some countries have decided to impose a lockdown. Until now, we have not found a drug or vaccine that can be used to overcome the spread of the COVID-19 virus. The purpose of this research is to be able to estimate the number of active cases in the addition of COVID-19 cases in Indonesia. This research will be tried using Backpropagation and Linear Regression methods. The results of prediction of active cases with Backpropagation gave the results of additions and decreases that were not too significant, while the results of prediction of active cases with Linear Regression showed that the addition of cases for each day experienced an increase in active cases.